The influence of testing angle on the biomechanical properties of the rat supraspinatus tendon. Issue 16 (8th December 2016) - Newton, Michael D.; Davidson, Abigail A.; Pomajzl, Ryan; Seta, Joseph; Kurdziel, Michael D.; Maerz, Tristan
Abstract: Rotator cuff tears are a common shoulder pathology. The rat supraspinatus tendon model is commonly employed for preclinical assessment of rotator cuff pathology or regeneration. However, there is a lack of a standardized biomechanical testing protocol; previous studies have tested the tendon at abduction angles ranging from −15° to 90°. This study aimed to assess the effect of abduction/testing angle on the biomechanical properties of the rat supraspinatus tendon. Fourty-eight shoulders ( n =12/group) from healthy Sprague-Dawley rats were randomized to 4 testing angle groups: 0° (corresponding to 90° abduction), 30°, 60°, and 90° (0° abduction). Biomechanical testing of the supraspinatus was performed, consisting of stress-relaxation and load-to-failure. Mechanical properties were calculated, and nonlinear tensile modeling was performed via the Quasilinear Viscoelastic (QLV) and Structurally Based Elastic (SBE) models. Results indicate that testing angle significantly affects supraspinatus tendon biomechanics. Stiffness and modulus significantly decreased with increasing testing angle (stiffness: 20.93±5.8 N/mm at 0° vs. 6.12±1.0 N/mm at 90°, P <.001; modulus: 59.51±34.0 MPa at 0° vs. 22.37±7.4 MPa at 90°, P =.002). Testing angle correlated significantly to ultimate strain, yield strain, and all coefficients of the SBE and QLV models, implying differences in collagen fiber crimp patterns and viscoelastic behavior as a function of testing angle. These results suggest that differences in testing methodology, in particular testing angle, significantly affect the measured mechanical properties of the supraspinatus tendon. Future studies may consider utilizing testing angles of 0°–30°, at which tendon stiffness is maximized, and full standardization of rat rotator cuff testing protocols is necessary.